2080. Differences in Hormonal Measures Among Transgender Individuals Assigned Male at Birth Switching from Tenofovir Disoproxil Fumarate/Emtricitabine to Tenofovir Alafenamide/Emtricitabine for Pre-Exposure Prophylaxis. (15th December 2022) - Patel, Nimish; Blumenthal, Jill; Burke, Leah; Chow, Karen; Pacheco, DeeDee; Stanczyk, Frank; Morris, Sheldon
Abstract: Background: There are concerns among transgender (TG) individuals about the effect of changing pre-exposure prophylaxis (PrEP) products on hormone concentrations. The objective of this study was to compare hormone concentrations among TG individuals assigned male at birth (AMAB) who switched from tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) to tenofovir alafenamide/emtricitabine (TAF/FTC) for PrEP. Methods: An observational cohort study was performed among a subset of TG individuals AMAB enrolled in a clinical trial evaluating TAF/FTC for PrEP. Inclusion criteria for this study were ≥18 years old, TG identity, HIV negative, use of both TDF/FTC and TAF/FTC for ≥12 weeks, and availability of stored blood samples for hormone measurement while on both medications. Estradiol, testosterone (total and free) and sex hormone binding globulin were quantified at two time points: once while on ≥12 weeks of TDF/FTC and after ≥12 weeks on F/TAF. Median hormone concentrations were compared using related-samples Wilcoxon Signed Rank Test. Results: Thirty participants met inclusion criteria with mean age of 35.9 ± standard deviation 9.7 years. There were 20 (67%) participants who identified as TG female. The remaining identified as gender non-conforming. Most participants self-identified as either Caucasian (40%), Hispanic or Latino/a/x (33%), Black (13.3%) or Asian (13.3%). Gender affirming therapy was used by 20 (67%) participants. The median (interquartile range, IQR) duration of TDF/FTC use before switching to TAF/FTC was 48 (15 – 60) weeks. Hormone values during TDF/FTC and TAF/FTC by use of gender affirming therapy is displayed in the Figure. Hormonal Values Before and After Switching PrEP Products, by Use of Gender Affirming Therapy Conclusion: Switching to TAF-based PrEP was not associated with significant changes in hormone values among TG individuals AMAB. Disclosures: Nimish Patel, PharmD, PhD, Gilead: Grant/Research Support Jill Blumenthal, MD, Gilead: Grant/Research Support Sheldon Morris, MD, Gilead: Grant/Research Support.